Suppression, surprise: galectin-10 and Treg cells - Rosenberg, Helene F. (American Society of Hematology, 2007)
The article by Kubach and colleagues in this issue of Blood includes not 1, but 2, intriguing and rather unexpected findings. As its title suggests, the authors compared expression patterns in CD4(+)CD25(+) regulatory T cells (Treg cells) with those in both resting and activated CD4(+)CD25(−) T-cell populations, and found prominent differential expression of the carbohydrate binding protein, galectin-10.